2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--17544
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Engineering Students from Underrepresented Groups Toward Service-Learning

Abstract: Ongoing student surveys, supplemented by interviews, reveal that service in general and servicelearning (S-L) in particular are more attractive to those from underrepresented groups in engineering than to their counterparts. Courses with service-learning projects have been integrated into existing required courses in engineering over the past six years in five departments at the University of Massachusetts Lowell. Entering engineering students have been sampled every fall with a "pre" survey, and then all stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…A study on "The Benefit of Outreach to Engineering Students" at Tufts University found that outreach activities resulted in enhanced self-confidence of women in particular [9], which is consistent with our findings that while they under-valued their skills before the outreach activity, they were more confident in them after the outreach. Another paper on "Attitudes of Engineering Students from Underrepresented Groups Toward Service Learning" at the University of Massachusetts at Lowell concludes that voluntary participation in such activities attracts women at a rate more than 3 times the underlying population [8]. Again, this is consistent with our findings that women expect to enjoy the activity more, and more positively link outreach with enhancing diversity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A study on "The Benefit of Outreach to Engineering Students" at Tufts University found that outreach activities resulted in enhanced self-confidence of women in particular [9], which is consistent with our findings that while they under-valued their skills before the outreach activity, they were more confident in them after the outreach. Another paper on "Attitudes of Engineering Students from Underrepresented Groups Toward Service Learning" at the University of Massachusetts at Lowell concludes that voluntary participation in such activities attracts women at a rate more than 3 times the underlying population [8]. Again, this is consistent with our findings that women expect to enjoy the activity more, and more positively link outreach with enhancing diversity.…”
Section: Discussionsupporting
confidence: 87%
“…Two previous ASEE conference papers specifically address a gendered effect on undergraduates involved in outreach activities, and another paper uses the VIE framework to design a survey on an outreach experience at Clemson, although gender differences were not examined [4]. A paper on "Attitudes of Engineering Students from Underrepresented Groups Toward Service Learning" at the University of Massachusetts at Lowell concludes that voluntary participation in such activities attracts women at a rate more than 3 times the underlying population, and that including such opportunities may be a way to attract and retain more underrepresented students [8]. Another paper focused on "The Benefit of Outreach to Engineering Students" at Tufts University found that outreach activities resulted in enhanced self-confidence of women in particular [9].…”
Section: Introductionmentioning
confidence: 99%
“…The PFEAS has been widely used across all engineering disciplines. Other assessment tools that were drawn from in the development of EPRA include the Academic Pathways of People Learning Engineering Survey (APPLES) 31 , the Scale of Service Learning Involvement 32 , NESLOS 22 , the Wabash Student Experiences Survey 33 , the Attitudes Towards Service Learning Survey 34 , the Intercultural Development Inventory (IDI) 35 , and the Sustainable Engineering via Service-Learning (SESL) survey instrument 36 . Table 6 in Appendix A summarizes the sources of the items used in the development of EPRA.…”
Section: Development Of the Engineering Professional Responsibility Assessment Toolmentioning
confidence: 99%
“…Similar to active learning, studies have shown that PBSL in engineering correlates with increases in technical knowledge 5 , professional skills such as teamwork, communication, and leadership 6 , and increased views of social responsibility 7 . Additionally, PBSL as a way to use engineering to help others may be more attractive to women and underrepresented minority students, helping to attract and retain a more diverse student body in engineering [8][9][10] . In the context of this course, PBSL was used to help show students that engineering can be used to help others in direct ways and that there are many local opportunities to have positive impacts with the skills that they are learning as engineering students.…”
Section: Introductionmentioning
confidence: 99%